Novel ABS-based binary and ternary polymer blends for material extrusion 3D printing. Issue 17 (28th July 2014) - Rocha, Carmen R.; Torrado Perez, Angel R.; Roberson, David A.; Shemelya, Corey M.; MacDonald, Eric; Wicker, Ryan B.
Abstract